Facile fabrication of highly porous Co3O4 nanobelts as anode materials for lithium-ion batteries. Issue 12 (25th January 2016) - Zheng, Fangcai; Shi, Kai; Xu, Shihao; Liang, Xianyu; Chen, Youcun; Zhang, Yuanguang
Abstract : Highly porous Co3 O4 nanobelts were successfully synthesized by using a hydrothermal technique, followed by calcination of the Co(OH)2 precursor. Abstract : Highly porous Co3 O4 nanobelts were successfully synthesized by using a hydrothermal technique, followed by calcination of the Co(OH)2 precursor. The as-prepared Co3 O4 nanobelts were analyzed by scanning electron microscopy, X-ray power diffraction, transmission electron microscopy, and Brunauer–Emmett–Teller methods. The electrochemical properties of porous Co3 O4 nanobelts were examined by cyclic voltammetry and galvanostatic charge–discharge studies. Owning to the unique 2D structural features, the Co3 O4 nanobelts exhibited a high specific capacity of 857 after 60 cycles at a current density of 100 mA g −1, and good cycling stability. These exceptional electrochemical performances could be attributed to the remarkable structural feature with a high surface area and large amounts of nanopores within the surface of nanobelts, which can provide large contact areas between electrolyte and active materials for electrolyte diffusion, improve structural stability and buffer volume expansion during the Li + insertion/extraction processes.